Frequency-dependent avoidance movement of glass catfish in response to sinusoidal electrical stimulation and associated spiking patterns of electroreceptors - Adachi, Yu; Tateno, Katsumi (Biology Open, 2023)
The glass catfish is a freshwater fish with electroreceptors on its body surface. In this study, we investigated its behavioral response to sinusoidal electrical stimulation with a dipole wider than its body length and the spiking patterns of its electroreceptors. We observed that sinusoidal electric stimulation with a large dipole distance elicited in the glass catfish an avoidance movement whose frequency range is frequency-dependent. The movements were prominent in the frequency range between 10–20 Hz. When the stimulation strength increased, the movements were also found in the low-frequency range. In electrophysiological experiments, periodic interspike intervals of the electroreceptors were modulated by sinusoidal electrical stimuli. The stimulation introduced irregularity in the spiking patterns. The local variability of the spike modulations was significantly higher in the frequency range of 4–40 Hz and was particularly sensitive at 20 Hz. The avoidance movements and an increase in the local variability in the spike patterns were found around 20 Hz. Our results indicate that the glass catfish avoids sinusoidal electrical stimulation in a frequency-dependent manner, and this is associated with local modulations in the spiking patterns of the electroreceptors.